2016
DOI: 10.1093/mnras/stw332
|View full text |Cite
|
Sign up to set email alerts
|

The scale-dependence of halo assembly bias

Abstract: The two-point clustering of dark matter halos is influenced by halo properties besides mass, a phenomenon referred to as halo assembly bias. Using the depth of the gravitational potential well, V max , as our secondary halo property, in this paper we present the first study of the scale-dependence assembly bias. In the large-scale linear regime, r 10Mpc/h, our findings are in keeping with previous results. In particular, at the low-mass end (M vir < M coll ≈ 10 12.5 M /h), halos with high-V max show stronger l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 72 publications
(86 reference statements)
4
66
1
Order By: Relevance
“…Additionally, these studies have not demonstrated the physical origin of the remaining assembly bias signal. Our results differ from those of Sunayama et al (2016), which find that splashback subhaloes have little effect on the MCF at large distances (R 10 h −1 Mpc). Sunayama et al (2016) used the same simulation and underlying halo catalogues as this paper, so this difference is likely due to the fact that their samples are defined by M vir (see section 4.2) and their use of halo bias ratios to measure assembly bias.…”
Section: Comparison With Previous Workcontrasting
confidence: 99%
See 1 more Smart Citation
“…Additionally, these studies have not demonstrated the physical origin of the remaining assembly bias signal. Our results differ from those of Sunayama et al (2016), which find that splashback subhaloes have little effect on the MCF at large distances (R 10 h −1 Mpc). Sunayama et al (2016) used the same simulation and underlying halo catalogues as this paper, so this difference is likely due to the fact that their samples are defined by M vir (see section 4.2) and their use of halo bias ratios to measure assembly bias.…”
Section: Comparison With Previous Workcontrasting
confidence: 99%
“…The figure shows that splashback subhaloes cannot account for the entirety of assembly bias, although they contribute about two thirds of the signal. This is consistent with conclusions of the previous studies (Wang et al 2009;Sunayama et al 2016). The novel feature of this analysis is that we find a similar effect for two independent definitions of the splashback haloes: using evolutionary trajectories ( §2.3.1) and using non-spherical 3D splashback shells identified using the SHELLFISH code ( §2.3.2).…”
Section: Subhalo Definitionsupporting
confidence: 91%
“…As with CIC, the annuli have a depth in the redshift dimension of 10 h −1 Mpc, corresponding to a velocity difference of ∆v = 1000 km s −1 . As with CIC, this geometry is chosen in order to probe the immediate environments of haloes, particularly on scales where assembly bias has already been shown to induce a feature in galaxy clustering (e.g., Hearin et al 2016;Sunayama et al 2016). We have experimented with moderately different annular dimensions and obtained qualitatively similar results in all cases.…”
Section: Counts-in-annuli (Cia) Statistic P(n Cia )mentioning
confidence: 88%
“…For the primary results that we present in this paper, we use r CIC = 2h −1 Mpc and a maximum relative velocity of ∆v = 1000 km s −1 , corresponding to a half-length of L = 10h −1 Mpc, assuming velocities are only due to the Hubble flow. We choose cylinders of a transverse radius r CIC on the order of a few h −1 Mpc in order to include galaxy companions separated by a scale on which assembly bias is known to introduce a distinct feature in halo clustering Zentner et al 2019;Sunayama et al 2016). We have experimented with a variety of alternative cylinder radii and depths, finding that our results remain qualitatively similar.…”
Section: Counts-in-cylinders (Cic) Statistic P(n Cic )mentioning
confidence: 94%
“…Ultimately, neglecting assembly bias in the modelling can lead to inferences that are systematically and significantly biased (Zentner et al 2014). This effect should be particularly strong for small-scale ∆Σ measurements that probe the dark matter halo structure, but can also have a non-negligible impact on intermediate scales (Sunayama et al 2016).…”
Section: Galaxy Assembly Biasmentioning
confidence: 99%